The impact of Rational-Emotive Counseling Group Model to Modify the Delinquency of Javanese Students - Tajri, Imam; Chandra, Evi Kartika (Islamic Guidance and Counseling Journal, 2018)
A Model of Rational-Emotive Counseling Group to Modify the Delinquency of Javanese Senior High School Students in Semarang City. Delinquency is a maladaptive action with both psycho-individual and psycho-social consequences. The factor that can cause student delinquency is the irrational belief. This research aimed to test the effectiveness of rational-emotive counseling group model in modifying delinquency. This research was conducted using quasi experiment with Ã¢â‚¬Å“patched-upÃ¢â‚¬Â design. As a whole, the results of the research show that: 1. Rational-Emotive Counseling Group model is the result of RET application in a group setting, whose components include: structure, input, process, output, evaluation, and follow-up, 2. Rational-Emotive Counseling Group is effective in modifying of delinquency. Further research should be conducted on different ethnicities, educational levels, and types of school.